The Influence of Emotional Regulation on Family Harmony in Married Couples Who Have No Children in Padang City - Gefri Dariando; Zulian Fikry (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Marriage is one of the most important moments in human life. Married couples often desire to have children to complete their family. This study aims to determine the influence of emotion regulation on family harmony among childless couples in Padang City and the differences in its influence based on gender. This research used a quantitative method with a correlational quantitative approach. The population in this study was married couples without children in Padang City. The sampling technique used in this study was snowball sampling with 60 respondents. The instrument in this study used the emotion regulation scale by Gross (2007) which was then adapted into Indonesian by Rajagukguk (2021). Family harmony was measured using the family harmony scale developed by Kavikondala et al. (2016) adapted into Indonesian by Fauzia, Hartini, Hendriani, and Fajriyanthi (2021). Data was collected by distributing questionnaires online using Google Forms and offline using questionnaires, then the data was processed using simple linear regression analysis with the help of IBM SPSS 20. The results of the hypothesis test showed a significant result of 0.039 < 0.05, which means there is a positive influence of emotion regulation on family harmony. The higher the emotion regulation of the couple, the higher the level of family harmony. This indicates that Ha is accepted and H0 is rejected. Based on gender differences, it was found that in men, the results were significant 0.001 < 0.05, which means there is an influence of emotion regulation on family harmony in childless males, so Ha is accepted and H0 is rejected. Conversely, in women, the test results were not significant 0.576 > 0.05, which means there is no relationship between emotion regulation and family harmony in females, so Ha is rejected and H0 is accepted.